Komuniciranje Prirodoslovnega muzeja Slovenije z javnostjo - Činč Juhant, Breda (Scopolia, 2021)
The museum's mission is a public service and so the Slovenian Museum of Natural History has been communicating with the public since its official opening in 1831. Up till now, forms and the extent of communication have changed and public programs have become increasingly extensive. The museum took into account the need for diverse communication relative to its target groups (ordinary visitors, professionals). More and more diverse programs were created, as made possible by the museum's employment and organization structure. The first museum pedagogue was employed in 1963. Today the field of communication is covered by the Public Relations Department and is significantly upgraded with activities and official duties of curators and the Special Library’s participation. Therefore, the article covers not only Public Relations Department, but attempts to present the museum's overall communication with the public, although inadequately staffed.
Keywords: Muzeji; Prirodoslovni muzej Slovenije